2018
DOI: 10.3233/cbm-170495
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol enhances the effects of ALA-PDT on skin squamous cells A431 through p38/ MAPK signaling pathway

Abstract: Our study demonstrated that Res could enhance the effect of ALA-PDT against skin cancer cells through p38/ MAPK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Moreover, resveratrol dose-dependently increased both apoptotic and necrotic cells after 24 hr treatment of two melanoma cell lines [108]. In addition, resveratrol also inhibited the growth of squamous cell carcinoma cells (A431 cell line) [81]. Resveratrolinduced apoptosis and inhibition of cell proliferation were also observed in human head and neck squamous cell carcinoma cell lines, e.g., FaDu, Cal27, and Det562 cell lines [111].…”
Section: Anticancermentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, resveratrol dose-dependently increased both apoptotic and necrotic cells after 24 hr treatment of two melanoma cell lines [108]. In addition, resveratrol also inhibited the growth of squamous cell carcinoma cells (A431 cell line) [81]. Resveratrolinduced apoptosis and inhibition of cell proliferation were also observed in human head and neck squamous cell carcinoma cell lines, e.g., FaDu, Cal27, and Det562 cell lines [111].…”
Section: Anticancermentioning
confidence: 89%
“…Both in vitro and in vivo studies have shown that resveratrol also inhibits proliferation, while stimulating apoptosis of cancer cells via several mechanisms. First, resveratrol induces apoptosis and phosphorylation of MAPK/ERK and MAPK/p38 in addition to increasing expression levels of caspase 3 and p53, while conversely, inhibition of p38 abolished its apoptotic effects [81,188]. It appears that resveratrol-induced phosphorylation of p53 and apoptosis is mediated by c-Jun NH2-terminal kinases because knockdown of c-Jun NH2-terminal kinase genes prevented both phosphorylation of p53 and apoptosis induced by resveratrol [189].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Unlike our results, other studies revealed that RES associated to ALA-PDT enhanced the effect of PDT on A431 cell proliferation and apoptosis. Moreover, the expressions of p-ERK, p-p53, p53 and caspase-3 increased after the combined therapy, suggesting an effect mediated by p38/MAPK pathway [55]. The extracts of Lumnitzera racemosa, Albizia procera and Cananga odorata photoactivated were cytotoxic against MCF-7 cells compared to the effects on non-tumor cells and induced apoptosis [56].…”
Section: Discussionmentioning
confidence: 96%
“…The HacaT non-tumorigenic keratinocyte cell line was used as a control and was acquired from the Experimental Zooprophylactic Institute of Lombardia and Emilia Romagna (Brescia, Italy). The HacaT cell line can be used as non-tumor control of the A431 cells (56)(57)(58)(59)(60) and it is considered a reliable model for skin diseases and for in vitro carcinogenesis of human skin keratinocytes (61,62). The HacaT and A431 cell lines were cultured under the same culture conditions to prevent differences in phototoxicity related to different growth mediums.…”
Section: Methodsmentioning
confidence: 99%